Long COVID: Is there a kidney link? - Garrett, Raymond E.; Palacio, Carlos H.; Bar-Or, David (Frontiers in Medicine, 2023)
Metabolic causes such as altered bioenergetics and amino acid metabolism may play a major role in Long COVID. Renal-metabolic regulation is an integral part of these pathways but has not been systematically or routinely investigated in Long COVID. Here we discuss the biochemistry of renal tubular injury as it may contribute to Long COVID symptoms. We propose three potential mechanisms that could be involved in Long COVID namely creatine phosphate metabolism, un-reclaimed glomerular filtrate and COVID specific proximal tubule cells (PTC) injury-a tryptophan paradigm. This approach is intended to allow for improved diagnostics and therapy for the long-haul sufferers.